Preparation Characterization and Antibacterial Studies of Chelates of Schiff Base Derived from4-Aminoantipyrine, Furfural and o-phenylenediamine - M. S. Suresh; V. Prakash (E-Journal of Chemistry)
A new series of transition metal complexes of Mn(II), Co(II), Ni(II), Cu(II) and Zn(II) were synthesized from the Schiff base ligand derived from 4-aminoantipyrine, furfural and o-phenylenediamine. The structural features were derived from their elemental analyses, infrared, UV-visible spectroscopy, NMR spectroscopy, thermal gravimetric analyses, ESR spectral analyses and conductivity measurements. The data of the complexes suggested square planar geometry for the metals with primary valency two. Antimicrobial screening tests were performed against bacteria. The comparative study of the MIC values of the Schiff base and its metal complexes indicate that the metal complexes exhibit greater antibacterial activity than the free ligand.